Answer: " x= \frac{18}{41} " ; {x\\eq \frac{-5}{3} ; 6}.
Explanation:
To solve: We cross-factor multiply:
that is:
"
" ;
; {
,
}.
___
So: both of the denominators cannot equal 0; since one cannot "divide by zero" ;
So,
; and:
;
So: Consider:
3x + 5 = 0 ; Solve for x (one of the values that x cannot equal):
Subtract each side of the equation by 5 ;
3x + 5 − 5 = 0 − 5 ;
to get: 3x = -5 ;
Now: Divide each side of the equation by 3; to isolate x
on one side of the equation; & to solve for x :
3x / 3 = -5 /3 ; to get: x= -5/3 ; so: "
" ;
___
Then: Consider: x + 6 = 0 ;
Solve for x (one of the values that x cannot equal):
Subtract each side of the equation by 6; to isolate x on one side of the equation; & to solve for x :
x + 6 − 6 = 0 − 6 ;
to get "x = -6 " ; so: "
" .
___
Now: Cross-factor multiply:
(9x − 7)(x + 6) = (3x + 6)(3x − 4) ;
___
Note the following:
(a + b)(c + d) = ac + ad + bc + bd ;
___
Let us start with the 'left-hand' side of the equation:
(9x*x) + (9x*6) + (-7*x) + (-7*6) ;
9x² + 55x + (-7x) + (-42) ;
→ 9x² + 55x − 7x − 42 ;
Combine the "like terms":
+ 55x − 7x = + 48x ;
Rewrite: → 9x² + 48x − 42 ;
___
Then: Let's continue with the 'right-hand' side of the equation:
(3x + 6)(3x − 4) ;
(3x*3x) + (3x*-4) + (6*3x) + (6*-4) ;
9x² + (-12x) + (18x) + (-24) ;
→ 9x² − 12x + 19x − 24 ;
Combine the "like terms" :
-12x + 19x = + 7x ;
Rewrite:
→ 9x² + 7x − 24 ;
Now, rewrite the entire equation:
9x² + 48x − 42 = 9x² + 7x − 24 ; and simplify:
-9x² − 7x + 24 = - 9x² − 7x + 24 ;
41x − 18 = 0 ;
Now, add 18 to each side of the equation:
41x − 18 + 18 = 0 + 18 ;
to get: 41x = 18 ;
Now, divide each side of the equation by 41; to isolate x on one side of the equation; & to solve for x :
41x / 41 = 18/ 41 ;
"
" ; {
;
} .
___
Hope this helps! Best wishes!
___